Risk factors for developing drug-related problems in patients with cardiovascular diseases attending Gondar University Hospital, Ethiopia - Ousman Abubeker Abdela; Akshaya Srikanth Bhagavathula; Henok Getachew; Yohannes Kelifa (Wolters Kluwer Medknow Publications, 2016)
Background: Cardiovascular diseases (CVDs) are often accompanied with comoribidities and complications leading to taking multiple drugs and thus are more liable to be exposed to drug-related problems (DRPs). DRPs can occur at any stages of medication process from prescription to follow-up treatment. However, a few studies have assessed the specific risk factors for occurrence of at least one potential DRP per patient with CVDs in sub-Saharan African region. Aim: We aim to assess the risk factors for developing potential DRPs in patients with CVDs attending Gondar University Referral Hospital (GUH). Methodology: This was a cross-sectional study. A structured systematic data review was designed focusing on patients with CVDs (both out and inpatients) with age >18 years of both genders attending GUH from April to June 2015. All DRPs were assessed using drugs.com and Medscape. The causes of DRPs were classified using Pharmaceutical Care Network Europe version 6.2. Risk factors that could cause DRPs were assessed using binary logistic regression showing odds ratio with 95% confidential interval. Statistical significance was set at P< 0.05. Results: A total of 227 patients with CVDs were reviewed with a mean age of 52.0 ± 1.7 years. Majority were females (143, 63%), outpatients (133, 58.6%), and diagnosed with heart failure (71, 31.3%). Diuretics (199, 29.5%) were the most commonly prescribed drugs. A total of 265 DRPs were identified, 63.4% of patients have at least one DRP (1.17 ± 1.1). The most common DRPs were found to be an inappropriate selection of drug (36.1%) and dose (24.8%). The most identified risk factors causing DRPs were: Need of additional drug therapy and lack of therapeutic monitoring. Conclusion: The most identified risk factors for developing DRPs were the need of additional drug therapy and lack of therapeutic monitoring. There is a need for clinical pharmacist interventions to monitor and prevent the risk of developing DRPs and contribute to improve the clinical outcome in patients with CVDs.